SAT0435 Plasma ptx3 levels correlate with systemic lupus erythematosus activity and are influenced by corticosteroids. (12th June 2018) - Ramirez, G.A.; Bozzolo, E.P.; Canti, V.; Bottazzi, B.; Mantovani, A.; Dagna, L.; Rovere-Querini, P.; Manfredi, A.A.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterised by a variable involvement of multiple organs and tissues. Acute and/or chronic vascular inflammation is not uncommon in patients with SLE and can significantly affect patient quality of life and survival. Specific markers of vascular inflammation in SLE are lacking. Pentraxin-3 (PTX3) is an evolutionarily conserved pattern recognition receptor expressed by multiple cell lines and is growingly recognised as a marker of the vessel response to injury. Glucocorticoids are known inducers of PTX3 in most tissues. The role of PTX3 as a biomarker in SLE is discussed. Objectives: To assess the potential informative role of PTX3 as a biomarker in patients with SLE with and without current or previous vasculitic manifestations and with active or quiescent disease. Methods: We enrolled 55 adult patients with SLE for a total of 60 samples. Samples were classified as taken from patients with active disease (SLE disease activity index, SLEDAI, ≥4) with or without active vasculitis and from patients with quiescent disease (SLEDAI <4). Further stratification was performed according to a history of lupus vasculitis. Five patients were bled twice under different conditions. Plasma PTX3 was measured by ELISA. Non-parametric tests were employed to compare PTX3 levels among groups. Results: PTX3 plasma levels were slightly but not significantly more elevated in patients with active vasculitis. PTX3 levels correlated with SLEDAI in the whole set of patients (p=0.007) and in those who were off corticosteroids (p<0.001), but not in patients receiving prednisone. PTX3 levels correlated with the dose of prednisone (p<0.001). Patients with >1 moderately-to-highly active (A, B) British Isles Lupus Assessment Group (BILAG) domain had significantly higher PTX3 levels than those with more limited disease activity extent (p=0.041). PTX3 also correlated with a 0.0–3.0 physician global assessment scale (PGA), with patient-reported visual analogue scale, and inversely with C4 levels (p=0.004, p=0.013, p=0.001 respectively). There was no significant correlation with age or disease duration nor with C-reactive protein (CRP). Similar to PTX3, CRP was higher in patients with >1 A/B BILAG domain (p=0.004), but did not correlate with SLEDAI or prednisone dose. Repeated samples showed a high intra-individual variability for PTX3, which unpredictably correlated with disease activity and prednisone dosage. Conclusions: Our data suggest that PTX3 is a marker of active disease extent rather than vascular inflammation in SLE and it shares this behaviour with CRP, another member of the pentraxin family. Nonetheless, PTX3 also specifically correlate with monoparametric indexes of activity such as SLEDAI. A high intra-individual variability and the effect of corticosteroids constitute potential limitations to future diagnostic applications of PTX3 in SLE. References: [1] Erreni M, et al. Immunol Rev2017. [2] Skare T, et al. Joint Bone Spine2015. [3] Assandri R, et al. Autoimmune Diseases2015. Disclosure of Interest: None declared